2009
DOI: 10.1074/jbc.m109.036293
|View full text |Cite
|
Sign up to set email alerts
|

SLIMMER (FHL1B/KyoT3) Interacts with the Proapoptotic Protein Siva-1 (CD27BP) and Delays Skeletal Myoblast Apoptosis

Abstract: The fhl1 gene encoding four-and-a-half LIM protein-1 (FHL1) and its spliced isoform, SLIMMER, is mutated in reducing body myopathy, X-linked myopathy with postural muscle atrophy, scapuloperoneal myopathy, and rigid spine syndrome. In this study we have identified a novel function for SLIMMER in delaying skeletal muscle apoptosis via an interaction with the proapoptotic protein Siva-1. Siva-1 was identified as a SLIMMER-specific-interacting protein using yeast two-hybrid screening, direct-binding studies, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…In addition to its interaction with TNFR superfamily members, Siva has also been shown to interact with anti-apoptotic Bcl-X L and sensitize MCF7 breast cancer cells to UV-induced apoptosis (48). Similarly, recent reports indicate that Siva can bind to lysophosphatidc acid recptor 2 (25, 40a), the adaptor protein TRAF2 in Jurkat T leukemia cells to modulate NF-B activity (14), pyrin in possibly human neutrophils, monocytes, and synovial cells (3) and with slimmer in skeletal myoblasts to delay apoptosis (8). Of two Siva splice variants (Siva-1 and Siva-2), the predominant form, Siva-1, retains the exon2 and it is believed to be critical for apoptotic activity (49).…”
mentioning
confidence: 91%
“…In addition to its interaction with TNFR superfamily members, Siva has also been shown to interact with anti-apoptotic Bcl-X L and sensitize MCF7 breast cancer cells to UV-induced apoptosis (48). Similarly, recent reports indicate that Siva can bind to lysophosphatidc acid recptor 2 (25, 40a), the adaptor protein TRAF2 in Jurkat T leukemia cells to modulate NF-B activity (14), pyrin in possibly human neutrophils, monocytes, and synovial cells (3) and with slimmer in skeletal myoblasts to delay apoptosis (8). Of two Siva splice variants (Siva-1 and Siva-2), the predominant form, Siva-1, retains the exon2 and it is believed to be critical for apoptotic activity (49).…”
mentioning
confidence: 91%
“…It seems that 2-h exposure caused more apoptosis than 1-h exposure. To validate the method, camptothecin that has been proven to be able to induce muscle cell apoptosis previously, 13 was included in the experiment as a positive control. It was found that exposure to camptothecin for 2 h also caused apoptosis in both cell lines.…”
Section: Caspase Activity Assaymentioning
confidence: 99%
“…Beside this location at the nuclear envelope, the various FHL1 isoforms have been reported at different locations within the cell: at the focal adhesions where it regulates cell migration via integrins (Robinson et al, 2003 ); in the sarcomeres where it interacts with MyBP-c as well as with titin and it is involved in sarcomere formation and in the stress-response signaling via activation of the MAPK signaling (McGrath et al, 2006 ; Sheikh et al, 2008 ); and in the nucleus where it interacts with various transcriptional factors (like NFAT proteins or RBP-J) involved in cell proliferation and differentiation but also with the pro-apoptotic protein Siva where it is involved in cell survival (Taniguchi et al, 1998 ; Schulz and Yutzey, 2004 ; Liang et al, 2008 ; Cottle et al, 2009 ).…”
Section: Proteins Involved In Edmdmentioning
confidence: 99%